Chronology, spatial organization, and mobility at Flattop Butte (5LO34), a prehistoric lithic quarry in the Central Plains of North America - Madden, Robert J., author; LaBelle, Jason M., advisor; Orsi, Jared, committee member; Van Buren, Mary, committee member (Colorado State University. Libraries, 2024)
This thesis reports on the results of an archaeological investigation at Flattop Butte (5LO34), a prehistoric lithic quarry located in northeastern Colorado. The site is an important location in the prehistory of the Central Plains of North America because it is the source of Flattop chalcedony, a cryptocrystalline tool stone used by ancient peoples for over 13,000 years, since the time that humans first entered the region. Sources of high-quality tool stone are uncommon, and separated by vast distances, in the Central Plains. This fact made Flattop Butte an essential destination for ancient, Indigenous Native American groups operating in the region, who visited it again and again for millennia, each time leaving evidence of their presence. Despite this importance, Flattop Butte has been the subject of only cursory archaeological investigation prior to the work reported here. Indeed, the vast majority of what is known about Flattop Butte comes not from the site itself, but rather from distant locations where Flattop chalcedony is found in the archaeological assemblages of ancient groups who used this lithic material for tool making. This thesis then represents an attempt to begin to lift the veil on Flattop Butte, and to explore it as an important archaeological site in its own right. It is a place that has much to say about the ancient peoples of the Central Plains, but only if some sense can be made of the seemingly incomprehensible mass of intermixed cultural materials and byproducts that were deposited on its surface and in its depths over hundreds of generations. With this goal in mind, the archaeological investigation reported here was designed to gather evidence at Flattop Butte relevant to three foundational research questions. The first is the chronology of use of the site, i.e., when was Flattop Butte used as a lithic source, and when were particular locations at the site used for these purposes? The second research question relates to spatial organization, i.e., where at the site did ancient groups carry out their lithic procurement activities, and did they segregate this work into separate, specialized activity areas? The final question relates to the effect, if any, that quarrying tool stone at Flattop Butte had on the mobility patterns of the ancient groups that visited the site for this purpose. Specifically, were these groups engaged in "embedded" procurement incidental to their subsistence rounds, having little impact on their overall mobility patterns, or were they engaged in "direct" procurement, making special trips to the site having significant impacts on their mobility patterns? Evidence relevant to these questions was gathered at Flattop Butte through survey and excavation. In addition, a literature review of the offsite use of Flattop chalcedony through time was conducted. The results of these efforts are reported here. On the question of chronology, it was found that Flattop Butte was continuously exploited as a lithic source in all prehistoric periods, for over 13,000 years. In addition, specific locations were identified at the site with evidence suggesting specific activities that took place at specific times, including a possible Paleoindian period secondary reduction workshop, two possible Archaic period workshops, and a Late Prehistoric period quarry pit. On the question of spatial organization, evidence was gathered suggesting that at various times ancient peoples organized their production of lithic materials at Flattop Butte into distinct task locations – quarry pit areas, secondary reduction workshops, and habitations – that were placed at a distance from each other on the butte. Finally, on the question of mobility, evidence suggests a high level of both logistical organization and labor investment in lithic production at Flattop Butte, as well as frequent long-distance transport of Flattop chalcedony, indicating that some of the groups that acquired Flattop chalcedony at the site were engaged in special-purpose "direct" procurement, around which their mobility patterns had to be arranged.
Keywords: lithics; Flattop Butte; quarry